Using Think Alouds, Think Afters, and Think Togethers to Research Adolescents’ Inquiry Experiences - Branch, Jennifer L. (Alberta Journal of Educational Research, 2006)
This article presents three research methods—Think Alouds, Think Afters, and Think Togethers—as ways of gathering data to describe the experiences of adolescents during instructional activities. These verbal report methods were used in two studies that examined the information-seeking processes of adolescents in Inuvik, Northwest Territories and Beaumont, Alberta. The first study revealed that participants needed both mediation (instruction and support) and practice to develop the skills and strategies needed for full-text searching of electronic encyclopedias. The second study revealed that students needed mediation (instruction and support) throughout an inquiry-based learning experience and that using Kuhlthau’s (1993) Information Search Process model as a guide for cognitive and affective mediation was useful. The Think Alouds, Think Afters, and Think Togethers allowed the researcher to collect data about the adolescents’ experiences of information-seeking; the data-gathering processes also provided the participants with a deeper understanding of their own experiences of instructional activities. I conclude the article with recommendations to enhance researchers’ use of verbal report methods with adolescents.